Persepsi Pelanggan Terhadap Takaful Keluarga dan Insurans Hayat : Kajian di Prudential BSN Takaful Keluarga dan Prudential Insurans Hayat - Salfarina, Omar (2010)
The purpose of this study was to examine customers' perceptions of family takaful and life insurance. A study was done at Prudential BSN Family Takaful and Prudential Life Insurance to assess the differences in the takaful and conventional insurance services. Although takaful has been introduced in a long time ago, but clearly seen in the Muslim community is more conventional view of insurance as a protection to guarantee their future. The main objective of this study is to examine customers' perceptions of savings and protection elements contained in Prudential BSN Family Takaful and Prudential Life Insurance, to review the level of customer awareness of the need and importance of life insurance and family takaful and review customer perception of the role of Syariah Supervisory Council in monitoring the implementation of takaful system in Malaysia follow the syariah principles. Qualitative methods are used where the survey questionnaires were distributed to the clients of Prudential BSN Family Takaful and Prudential Life Insurance customers within the state of Perlis. The analysis is made in the form of frequency distribution, statistic descriptive, ANOVA and Pearson Correlation to achieve the objective. The study found that the perception of customers of Prudential BSN Family Takaful and Prudential Life Insurance will guarantee savings and protection to them. Syariah Supervisory Council also plays an important role in ensuring the implementation of takaful in Malaysia is based on syariah principles.